Globally Aging Cortical Spontaneous Activity Revealed by Multiple Metrics and Frequency Bands Using Resting-State Functional MRI - Xing, Xiu-Xia (Frontiers in Aging Neuroscience, 2021)
Most existing aging studies using functional MRI (fMRI) are based on cross-sectional data but misinterpreted their findings (i.e., age-related differences) as longitudinal outcomes (i.e., aging-related changes). To delineate aging changes of human cerebral cortex, we employed the resting-state fMRI (rsfMRI) data from 24 healthy elders in the PREVENT-AD cohort, obtaining five longitudinal scans per subject. Cortical spontaneous activity are measured globally with three rsfMRI metrics including its amplitude, homogeneity and homotopy at three different frequency bands (slow-5: 0.02 - 0.03Hz, slow-4: 0.03 - 0.08Hz, slow-3 band: 0.08 - 0.22Hz). General additive mixed models revealed a universal pattern of the aging-related changes for the global cortical spontaneous activity, indicating increases of these rsfMRI metrics during aging. This aging pattern follows specific frequency and spatial profiles where higher slow bands show more nonlinear curves and the amplitude exhibits more extensive and significant aging-related changes than the connectivity. These findings provide strong evidence that the cortical spontaneous activity is aging globally, inspiring its clinical utility as neuroimaging markers for neruodegeneration disorders.